Delay-Optimal Coding for Secure Transmission over Parallel Burst Erasure Channels with an Eavesdropper - Frank, Anna (Proceedings / IEEE International Symposium on Information Theory, 2020)
For streaming applications, we consider parallel burst erasure channels in the presence of an eavesdropper. The legitimate receiver must perfectly recover each source symbol subject to a decoding delay constraint without the eavesdropper gaining any information from his observation. For a certain class of code parameters, we propose delay-optimal M-link codes that recover multiple bursts of erasures of a limited length, and where the codes provide perfect security even if the eavesdropper can observe a link of his choice. Our codes achieve the maximum secrecy rate for the channel model.